Perancangan Game Edukasi Pengetahuan Dasar Untuk Anak Usia Dini Berbasis Android di PAUD Tunas Bahari Padang - Irsyadunas Irsyadunas; Indah Dwi Suryani; Thomson Mary (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2021)
Educational games are games that have educational content that is educational. Basic knowledge educational game for early childhood based on android is made for PAUD Tunas Bahari Padang children. Where in the current state of Covid19, PAUD Tunas Bahari Padang children are eliminated from the learning process at school, therefore of course they really need this educational game to learn while playing. This basic knowledge educational game for early childhood based on android is designed using the SDLC model. The SDLC model is a model that has a characteristic that the work of each phase must be done first before moving on to the next phase. Where the phases are analysis, design, code generation, application testing, maintenance and repair. The design of basic knowledge educational games for early childhood based on android in PAUD Tunas Bahari Padang was made using android studio software and designed using photoshop, and the testing used black box testing.